Investigation into the protective effects of Naringenin in phthalates-induced reproductive damage - Taslidere, A.; Turkmen, N. B.; Ciftci, O.; Aydin, M. (Verduci Publisher, 2022)
OBJECTIVE: Di-n-butyl phthalate (DBP) is a ubiquitous environmental pollutant, extensively used as a plasticizer in many products, including plastics. cosmetics. and medical devices. Naringenin (NAR) is a flavonoid belonging to the flavanones subclass. It is widely distributed in several citrus fruits, bergamot, tomatoes, and other fruits. It is also found in its glycoside form (mainly naringin). Several biological activities have been ascribed to this phytochemical: antioxidant, antitumor, antiviral, antibacterial, anti-inflammatory, antiadipogenic, and ca rdioprotective effects. This study hypothesized that phthalates' possible reproductive damage mechanism is oxidative attack, and naringenin could have a protective effect against radical forms in the body through its antioxidant properties. MATERIALS AND METHODS: Thirty-two male rats were used in our study (n=8 each). Rats were randomly divided into four groups: Control, DBP, DBP +NAR and NAR. Phthalate (DBP) and NAR were administered through gastric oral gavage (phthalate group 500 mg/kg/day DBP: NAR group 50 mg/kg/day NAR). At the end of four weeks. testis tissue samples were taken under anesthesia. Testis tissue and blood samples were collected from the four groups in this study. Histological, biochemical and spermatological analyses were conducted. RESULTS: Tissue samples from the control and NAR groups showed normal histological appearance on light microscopy. The DBP group exhibited deterioration in seminiferous tubules, vascular congestion in capsule, vascular congestion between the seminiferous tubules, edema in the intestinal area and vacuolization. arrested spermatocytes in different stages of division; sloughing of cells into the seminiferous tubular lumen was observed. it was also observed that NAR treatment significantly inhibited and prevented the histopathological damage caused by DBP. Tissue TBARS, antioxidant parameters, sperm motility, sperm density and abnormal spermatozoon ratios were determined. As a result, it was shown that DBP caused oxidative damage by increas- ing TBARS levels and decreasing antioxidant parameters. increased abnormal sperm rate and decreased sperm motility. and concentration and histopathological damage, so the antioxidant activity of naringenin inhibited this damage. CONCLUSIONS: DBP had toxic effects in rat testis tissue: NAR treatment ameliorated these effects. Further studies are warranted to confirm our findings.
Keywords: Di-n-butyl phthalate; Naringenin; Oxidative stress; Spermiotoxicity; Testicular damage